Changes in rainfall seasonality inferred from weathering and pedogenic trends in mid-Miocene paleosols of La Tatacoa, Colombia - Salazar Jaramillo, Susana; Śliwiński, Maciej G.; Hertwig, Andreas; Garzón, Cristian C.; Gómez, Christian F.; Bonilla, German E.; Guerrero, Javier (Global and planetary change, 2022)
The authigenic clay mineral assemblage of paleosol profiles and trends in their bulk geochemical evolution provide insight into the intensity of past chemical weathering regimes. These climate-sensitive weathering products can be used to interpret regional changes of the soil moisture regime, which in turn reflects upon the nature of rainfall seasonality (e.g., unimodal vs. bimodal). A conspicuous color change in the overbank deposits and paleosols of the mid-Miocene Honda Group of La Tatacoa, Colombia, is suggestive of a climatic transition which affected the fauna of La Venta - a mid-Miocene fossiliferous site and significant component of the South American Land Mammal Age (SALMA) classification. This study aims to determine how the paleopedology of this region records the climatic transition that modified the annual patterns of rainfall and soil moisture, forcing a change from the gray-colored paleosols hosted by the La Victoria Formation (~13.6 to ~13.1 Myr) to the red-beds of the Villavieja Formation (~13.1 to 12.0 Myr). In the La Victoria profile, the pedogenic fraction of the clay assemblage indicates that vermiculite, chlorite/HIV mixed-layered clays and high concentrations of base cations (Ca2+, Mg2+, Na+) developed in a poorly drained paleosol under reducing (low Eh) and above-neutral pH conditions. By contrast, the presence of kaolinite, goethite and hematite in the red-beds paleosols implies more oxidizing conditions (high Eh), whereas pedogenic vermiculite and smectite suggest a pH close to or mildly below neutral. A common detrital source (parent material) is inferred for both sets of paleosols. However, more intense chemical weathering towards aluminium rich clay in the Villavieja red-bed fossil soils indicates a change in soil humidity from a poorly drained soil environment of a seasonally flooded wetland system to an alternating regime of humidity and drought on a better drained floodplain. The variation in soil moisture is consistent with a change in seasonality from a unimodal rainfall regime in the case of the La Victoria paleosols to bimodal conditions in the case of the paleosols of the Villavieja Fm. After the establishment of a fully glaciated Antarctica and the global climate transition into the Mi-4 glacial stage at ~13.1 Ma, an increased rate of continental weathering along the paleotropical fringe could have been caused by a stronger temperature gradient between the equator and South Pole, shifting the Intertropical Convergence Zone northward and the rainfall patterns with it.
Gesehen am 04.10.2022